"If You Don't Like Gay Marriage, Don't Get One!": A Qualitative Analysis of Attitudes Toward Same-Sex Marriage in South Australia. Issue 5 (20th October 2017) - Webb, Stephanie N.; Chonody, Jill; Kavanagh, Phillip S.
ABSTRACT: Prejudice against sexual-minority groups has continuously declined in Australia over the past several decades, yet inequality in marriage policy that denies legal recognition of same-sex relationships remains. Social role theory suggests this may be due in part to traditional beliefs about gender roles that fuel concerns regarding the ability of same-sex couples to raise children because they violate these social norms and roles. The current study identified reasons behind support of, or opposition to, same-sex marriage. Data were collected from a community sample ( n = 536) in South Australia through an open-ended question included on a larger survey. Content analysis suggested that gender role norms do play a part in negative attitudes toward same-sex marriage as well as perceptions of same-sex couples' ability to raise children. Our findings also revealed heteronormativity embedded in the responses of participants both for and against marriage equality. Implications for advocacy efforts focused on marriage equality, parenting by same-sex couples, and the focus for future research endeavours in this substantive domain are discussed.